Study of adsorption states in ZnO–Ag gas-sensitive ceramics using the ECTV curves method - Lyashkov, A. Yu. (Technology and design in electronic equipment, 2013)
The ZnO–Ag ceramic system as the material for semiconductor sensors of ethanol vapors was proposed quite a long time ago. The main goal of this work was to study surface electron states of this system and their relation with the electric properties of the material. The quantity of doping with Ag2O was changed in the range of 0.1–2.0% of mass. The increase of the Ag doping leads to a shift of the Fermi level down (closer to the valence zone). The paper presents research results on electrical properties of ZnO–Ag ceramics using the method of thermal vacuum curves of electrical conductivity. Changes in the electrical properties during heating in vacuum in the temperature range of 300–800 K were obtained and discussed. The increase of Tvac leads to removal of oxygen from the surface of samples The oxygen is adsorbed in the form of O2– and O– ions and is the acceptor for ZnO. This results in the lowering of the inter-crystallite potential barriers in the ceramic. The surface electron states (SES) above the Fermi level are virtually uncharged. The increase of the conductivity causes desorption of oxygen from the SES settled below the Fermi level of the semiconductor. The model allows evaluating the depth of the Fermi level in the inhomogeneous semiconductor materials.